Sam68 RNA Binding Protein Is an In Vivo Substrate for Protein Arginine N-Methyltransferase 1 - Côté, Jocelyn (The American Society for Cell Biology, 2003)
RNA binding proteins often contain multiple arginine glycine repeats, a sequence that is frequently methylated by protein arginine methyltransferases. The role of this posttranslational modification in the life cycle of RNA binding proteins is not well understood. Herein, we report that Sam68, a heteronuclear ribonucleoprotein K homology domain containing RNA binding protein, associates with and is methylated in vivo by the protein arginine N-methyltransferase 1 (PRMT1). Sam68 contains asymmetrical dimethylarginines near its proline motif P3 as assessed by using a novel asymmetrical dimethylarginine-specific antibody and mass spectrometry. Deletion of the methylation sites and the use of methylase inhibitors resulted in Sam68 accumulation in the cytoplasm. Sam68 was also detected in the cytoplasm of PRMT1-deficient embryonic stem cells. Although the cellular function of Sam68 is unknown, it has been shown to export unspliced human immunodeficiency virus RNAs. Cells treated with methylase inhibitors prevented the ability of Sam68 to export unspliced human immunodeficiency virus RNAs. Other K homology domain RNA binding proteins, including SLM-1, SLM-2, QKI-5, GRP33, and heteronuclear ribonucleoprotein K were also methylated in vivo. These findings demonstrate that RNA binding proteins are in vivo substrates for PRMT1, and their methylation is essential for their proper localization and function.